Levosimendan: a general overview - Tarnowski, Michał; Wałcerz-Bajorska, Martyna; Brania, Paulina; Domoń, Dominik; Furtak, Kinga; Tarnowska, Monika; Kobierska, Anita; Myrda, Krzysztof (Medical Studies/Studia Medyczne, 2026)
Heart failure remains a major clinical and public health problem worldwide, associated with high morbidity and mortality, and frequent hospitalizations. Despite advances in pharmacological and device-based therapies, management of acute and advanced heart failure remains challenging, particularly in patients requiring inotropic support. Conventional catecholaminergic inotropes are associated with increased myocardial oxygen consumption, arrhythmias, and adverse prognosis. Levosimendan, a non-catecholaminergic inodilator, has emerged as an alternative therapeutic option. The aim of this review is to summarise current knowledge on levosimendan, with particular emphasis on its pharmacological properties, mechanisms of action, clinical applications, and safety profile. A better understanding of these mechanisms may help optimise the clinical use of levosimendan and identify patient populations most likely to benefit from this therapy.